2022
DOI: 10.1002/ijc.34386
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle long RNA markers of early‐stage lung adenocarcinoma

Abstract: Lung cancer screening by low‐dose computed tomography (LDCT) can improve mortality rates among high‐risk individuals, especially adenocarcinoma cases with characteristically poor prognosis, although high false‐positive rates have limited its clinical application. The objective of our study was to identify biomarkers for early‐stage lung adenocarcinoma (ie, tumor diameter <2 cm) through extracellular vesicle long RNA (evlRNA) sequencing. High throughput evlRNA sequencing and support vector machine (SVM) identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The methodologies employed for collection of blood samples, serum extracellular vesicle (EV) purification, RNA isolation, characterization of EVs, construction of evlRNA libraries and subsequent RNA-seq analysis closely adhere to those detailed in the previously cited work 12 . We explored the differentially expressed genes (DEGs) between the LUAD and control groups, which revealed a total of 145 upregulated and 363 downregulated DEGs ( p value < 0.05, fold change > 1.5).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodologies employed for collection of blood samples, serum extracellular vesicle (EV) purification, RNA isolation, characterization of EVs, construction of evlRNA libraries and subsequent RNA-seq analysis closely adhere to those detailed in the previously cited work 12 . We explored the differentially expressed genes (DEGs) between the LUAD and control groups, which revealed a total of 145 upregulated and 363 downregulated DEGs ( p value < 0.05, fold change > 1.5).…”
Section: Methodsmentioning
confidence: 99%
“…Combining liquid biopsy with AI methods holds significant promise for early-stage diagnosis 9 , 10 . Extracellular vesicle long RNA (evlRNA), identified as a candidate biomarker, is enriched in the blood of lung cancer patients compared to healthy controls, showing significant diagnostic value in early-stage LUAD patients 11 , 12 . However, many current liquid biopsies focusing on early cancer detection lack the sensitivity needed for reliable identification of early-stage cancers 13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that EVs can serve as biomarkers for the detection of precancerous lesions. Current methods for diagnosing early lung cancer using EVs are inclined towards the detection of miRNA or lncRNA carried by EVs [ 139 , 140 ]. For example, the elevated expression of miR-520c-3p and miR-1274b in lung cancer can be detected by EVs for the early diagnosis of NSCLC [ 139 ].…”
Section: Clinical Application Potential Of Liquid Biopsy In Lung Cancermentioning
confidence: 99%
“…It was found that miR-451a, miR-194-5p and miR-486-5p were significantly increased in EV in lung adenocarcinoma patients compared with healthy individuals, with an AUC of 0.993[ 31 ]. In another study, extracellular vesicle Long RNA (NFKBIA, NDUFB10, SLC7A7, ARPC5, SEPTIN9, HMGN1, H4C2, and Lnc-PLA2G1B-2) were regarded as signature of early NSCLC (diameter < 2 cm), and extracellular vesicle Long RNA can be used as a supplement to LDCT as a noninvasive biomarker for screening early NSCLC [ 32 ]. With the progression and change of the disease, the expression level of circulating ncRNA has a sensitive trend of change.…”
Section: The Origin Of Circulating Ncrnasmentioning
confidence: 99%